Exploring the path for patient organizations to participate in medical security for rare diseases - Dong, Tian-tian; Xie, Dong-yi (Frontiers in Public Health, 2025)
The participation of patient organizations in the construction of medical security systems for rare diseases is an important proposition in the theory of welfare pluralism, which indicates that individualized services and diversified connections of patient organizations can fully meet the multiple medical insurance needs of patients with rare diseases. In actual practice, however, patient organizations continue to experience institutional and structural difficulties, such as improper supervision, insufficient capacity and insufficient coordination. The theory of welfare pluralism and the developmental experience of foreign rare disease organizations have suggested that patient organizations should clarify the bridge positioning and specialized development path in the multi-subject cooperation of organizations providing medical security for rare diseases, thereby improving the efficient implementation of medical security policies for rare diseases.